Pregnancy spacing and fetal risk: associated factors, knowledge and attitude - Hamzah, Tengku Norbanee Tengku (Pusat Pengajian Sains Perubatam Universiti Sains Malaysia, 2008)
Objective: The aim of this study is to determine the prevalence and associated factors for short birth spacing among Malay won1en who delivered at Hospital Universiti Sains Malaysia (HUSM), Kota Bharu, Kelantan. Desig11: A cross-sectional study conducted from June to November 2005 Materials a11d 11tetltods: Three hundred and fifty five women were selected by systematic random sampling. An interview-guided questionnaire that included information on socio-demographic, obstetric, knowledge and attitude on family planning was conducted to the women and self-administered questionnaire was given to their husbands. Simple and multiple logistic regression analysis were used to determine the associated factors for short birth spacing. Results: The median birth spacing was 26 (IQR 28) months. The prevalence of short birth spacing was 45.1% (95%CI: 40.4, 49.8). Multiple logistic regression analysis showed that women are less likely to have short birth spacing with every one year increase in age ( OR=0.86, 95%CI 0.80, 0.92), women with short birth spacing had 1.46 times odds of every one unit increase in parity (OR=l.46, 95%CI 1.22, 1. 76), women with short birth spacing had 6.18 times odds of breastfeeding their babies for less than 1 year (OR=6.l8, 95%CI 3.59, 10.62), women with short birth spacing had 3.95 times odds of not using family planning methods between the second last and the last delivery (OR=3.95, 95%CI 2.21, 7.05) and women with a history of abortion between the second last and the last delivery were less likely to have short birth spacingcotnparcd to those with no history of abortion (OR=0.09, 95~1oCI 0.02, 0.34). However, women's knowledge and attitude on family planning as well as husband's factors were not significantly associated with short birth spacing. Collclusioll: The prevalence of short birth spacing among Malay won1en \Vho delivered at HUSM \Vas high. Therefore, birth spacing should be given more priority in the maternal, child health, family planning and nutrition programmes at all levels.